Development of Raw Material Base in the Production of Meat Products - Tangatarovich, Eshmuratov Marat; Kyzy, Amangeldieva Albina Salamat (American Journal of Biology and Natural Sciences, 2025)
Modern meat industry is one of the important sectors of the economy and plays a key role in ensuring food security of the population. The development of raw material base is crucial for increasing competitiveness and efficiency in this sphere. The article considers ways of expanding the raw material base, introduction of modern technologies and efficient use of resources.